Perceived Neighborhood Built Environment and Physical Activity in Urban Population in Chile - De Moraes-Ferrari, G (BioMed Central Ltd, 2025)
Background: Various indicators of neighborhood environmental perceptions are differently associated with physical activity (PA) domains, with notable variations by sex. However, few studies in Latin America have examined these associations across distinct PA domains. In this study, we analyzed the relationship between neighborhood environmental perceptions and PA in the domains of transportation and leisure among Chilean adults. Methods: This cross-sectional analytical study included 770 participants from the 2014–2016 Latin American Nutrition and Health Survey (ELANS). Perceptions of land use diversity, access to land use, street connectivity, walking and cycling infrastructure, aesthetics, safety from crime, and neighborhood traffic were assessed using the Neighborhood Environment Walkability Scale-Abbreviated (NEWS-A) questionnaire. PA was measured with the International Physical Activity Questionnaire-Long Form (IPAQ-LF), focusing on the transportation and leisure-time domains. Logistic regression and multiple linear regression models were used for the analysis. Results: Logistic regression analysis in men showed no association between neighborhood characteristics and PA in the transportation or leisure-time domains. However, for women, greater perception of facilities for walking or cycling was inversely associated with transportation PA (OR: 0.62; 95%CI: 0.42;0.92). In the multiple linear regression analysis, higher perceived traffic safety was associated with greater PA (min/week) for both transportation (β: 0.098; 95%CI: 0.005;0.192) and leisure time (β: 0.160, 95%CI: 0.012;0.309). For men, higher scores for perceived access to land use were inversely associated with leisure-time PA (β: -0.150, 95%CI: -0.266;-0.034). Conclusions: Different perceived neighborhood characteristics are associated with PA across various domains, with notable gender differences. A better perceived condition of traffic safety would promote urban population to engage in more transportation and leisure-time PA. Clinical trial number: ClinicalTrials.Gov NCT02226627. Retrospectively registered on August 27, 2014. Trial registration: ClinicalTrials.Gov NCT02226627. Retrospectively registered on August 27, 2014. © The Author(s) 2025.